Layanan Bimbingan dan Konseling Sosial dan Pribadi - Mufidah, Cindy Imroatul; Bariza, Marwa Fuha Alilatul; Aisyah, Shiva Nur; Sholekhah, Adistya Aliyus; Putri, Ratna Rucita (Lembaga Yasin AlSys, 2025)
This paper discusses the importance of personal and social guidance in individual development, especially for students, as social beings who are inherently engaged in social interactions. Guidance serves to help individuals recognize themselves, overcome problems, and adapt to their social environment. Through a qualitative literature study approach, this research finds that personal and social guidance aims to develop individuals' potential to become independent in decision-making. Various guidance techniques, such as individual and group counseling, are employed to facilitate student development. Despite challenges such as moral degradation among teenagers and rapid social changes, the role of counselors remains crucial in providing direction and support. In conclusion, personal and social guidance can help individuals develop a positive attitude and enhance their social interaction skills effectively.